2021
DOI: 10.1002/cti2.1261
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of SARS‐CoV‐2 antibody dynamics in New Zealand

Abstract: Objectives. Circulating antibodies are important markers of previous infection and immunity. Questions remain with respect to the durability and functionality of SARS-CoV-2 antibodies. This study explored antibody responses in recovered COVID-19 patients in a setting where the probability of re-exposure is effectively nil, owing to New Zealand's successful elimination strategy. Methods. A triplex bead-based assay that detects antibody isotype (IgG, IgM and IgA) and subclass (IgG1, IgG2, IgG3 and IgG4) response… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 34 publications
6
39
0
Order By: Relevance
“…A study by Liu, et al on 52 convalescent patients over a course of 6 months post symptom onset, reported that anti-S IgG remained detectable in more than 90% of patients [32]. In another study by Whitcombe et al, convalescent sera from patients with mild to moderate COVID-19 were collected up to 8 months post symptom onset [33]. It also showed that after 4 to 8 months 99% of the tested sera contained IgG antibodies against RBD and that 96% showed detectable titres of anti-S IgG [33].…”
Section: Adaptive Immune Responses In Asymptomatic Mild and Severe Cases Of Covid-19mentioning
confidence: 99%
“…A study by Liu, et al on 52 convalescent patients over a course of 6 months post symptom onset, reported that anti-S IgG remained detectable in more than 90% of patients [32]. In another study by Whitcombe et al, convalescent sera from patients with mild to moderate COVID-19 were collected up to 8 months post symptom onset [33]. It also showed that after 4 to 8 months 99% of the tested sera contained IgG antibodies against RBD and that 96% showed detectable titres of anti-S IgG [33].…”
Section: Adaptive Immune Responses In Asymptomatic Mild and Severe Cases Of Covid-19mentioning
confidence: 99%
“…To simulate remote blood sampling to accurately measure anti-RBD, IgG was also demonstrated using Mitra samplers. 21 Another group of researcher has developed an assay protocol to detect SARS-CoV-2 RBD-specific IgG antibodies in the existing newborn screening laboratory infrastructure. 6 Numerous research papers have been published on antibody detection during SARS-CoV-2 infection, offering vital clinical information.…”
Section: Applications In Covid-19mentioning
confidence: 99%
“…20 Traditionally, blood sample drawn by venepuncture was the requirement for laboratory-based assays, but with the development of newer assay techniques, only a small volume of finger-pricked blood suffice the sample volume. 6,[21][22][23] Immunoassays are well established for dried blood microsampling. A promising sensitivity and specificity was achieved when small-volume finger-stick capillary samples were analysed with modifications to two commercially available Covid-19…”
Section: Antigen Tests (Rapid Diagnostic Tests)mentioning
confidence: 99%
“…Antibodies to the Spike (S) protein and receptor-binding domain (RBD) persist for many months after infection, compared with antibodies to the nucleocapsid (N) protein [ 5 , 6 ], providing a rationale for the use of S protein-based assays in serosurveys. The overall serological testing algorithm was optimised for specificity given the low number of reported COVID-19 cases in New Zealand (2190 as of 6 January 2021) and the associated period prevalence of 0.04%, which limits the positive predictive value of tests with reduced specificity [ 7 ].…”
mentioning
confidence: 99%
“…1 ). Further analysis of the 18 seropositive samples with a multiplex bead-based assay that detects antibody isotype reactivity to RBD, S and N proteins [ 5 ] revealed a pattern consistent with infections that occurred weeks or months prior; a dominance of RBD and S protein IgG with few samples positive for N protein IgG, nor IgA or IgM against any of the three antigens ( Fig. 1 ).…”
mentioning
confidence: 99%